Acute and Critical Care Formulas and Laboratory Values - Varon, Joseph; Fromm, Jr., Robert E. (Springer New York : Imprint: Springer, 2014)
This pocket guide is a single-volume source of the most common and important formulas and laboratory values used in the daily practice of acute care and critical care medicine.  Information is presented in outline format and as tables, graphics, and algorithms to facilitate quick look up.  Acute and Critical Care Formulas and Laboratory Values is designed to help clinicians interpret clinical data, apply formulas, understand laboratory values, and integrate this information with their knowledge of pathophysiology to promote the delivery of evidence-based care. Essential formulas and laboratory values Multiple ways to derive a value, where appropriate Non-clinical formulas useful for understanding physiologic concepts or that underlie diagnostic tests or clinical measurement  included Chapters divided by organ system Practical appendixes of "Abbreviations" and "Key Telephone Numbers" A special "Notes" section for recording frequently used formulas.